2015
DOI: 10.3390/f6010183
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Wood Quality in White Spruce (Picea Glauca (Moench) Voss). Part I. Defining the Juvenile–Mature Wood Transition Based on Tracheid Length

Abstract: Estimations of transition age (TA) and juvenile wood proportion (JWP) are important for wood industries due to their impact on end-product quality. However, the relationships between analytical determination of TA based on tracheid length (TL) and recognized thresholds for adequate end products have not yet been established. In this study, we used three different statistical models to estimate TA in white spruce (Picea glauca (Moench) Voss) based on TL radial variation. We compared the results with technologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
2
14
1
1
Order By: Relevance
“…In a previous study, we found that a polynomial model that accounts for the autocorrelation among successive growth rings is a better choice than the piecewise model in determining TA based on TL [11]. However, the age span of the material used in this study did not allow using the polynomial model with TL.…”
Section: Transition Age and Juvenile Wood Proportionmentioning
confidence: 83%
See 3 more Smart Citations
“…In a previous study, we found that a polynomial model that accounts for the autocorrelation among successive growth rings is a better choice than the piecewise model in determining TA based on TL [11]. However, the age span of the material used in this study did not allow using the polynomial model with TL.…”
Section: Transition Age and Juvenile Wood Proportionmentioning
confidence: 83%
“…where Y ij = measured value of the WQA, µ = overall mean of the provenance, P i = random effect of provenance i, and ε ij = random error term associated with the j th tree of the i th provenance, ε ij~N (0, σ 2 residuals ). Intraclass correlation coefficients (ICC) were calculated from variance parameter estimates computed with the MIXED model using Equation (11). The intraclass correlation coefficient informs us about the proportion of the total variance explained by provenances [31,32].…”
Section: Variation and Ranking Among Provenancesmentioning
confidence: 99%
See 2 more Smart Citations
“…One way of generating these data is the time-consuming process of manually measuring cells from physically and chemically macerated wood under a light microscope [Fujiwara and Yang, 2000]. Alternatively, optical fibre analysers are used, which allow a rapid and automated analysis of samples, and this technique has been used to build up a picture of fibre geometry across different species [Li et al, 2011, Mvolo et al, 2015 and throughout a complete tree [Yemele et al, 2015]. These studies show that cell length varies from the centre of the tree, increasing through the juvenile wood and becoming relatively constant in mature wood.…”
Section: Background and Summarymentioning
confidence: 99%